Education to achieve sustainability-oriented development - Ubiratan D’Ambrosio (Desenvolvimento e Meio Ambiente, 2007)
Promoting proper Education so that society can seek and achieve sustainability-oriented development, in the broadest sense, is without any doubt an essentially political matter. It is, above all, a topic that leads to the following questions: how frequently, with which attitude, with which research and actions, can Academia suggest ways to that end? This article shows that the answer depends on recognizing the relationship between knowledge systems and human values. In general terms, one can say that this kind of Education, aiming to think ethical values and transdisciplinary knowledge at the same time, is ultimately what could be called Education for Peace – that is to say, a path leading the human being to a state of real conscience, only possible when both human knowledge and behavior are solidary.